Characterisation of the invasive tumour niche using astrocyte-glioblastoma organoids and decellularised human brain. (12th October 2019) - Diksin, Mohammed; Rowlinson, Jonathan; Kondrashov, Alexandar; Denning, Chris; Hughes, Jamie; Constantin-Teodo, Tim; Cui, Wei; Gell, Chris; Onion, David; Croxall, Nicola; Smith, Stuart; Rahman, Ruman
Abstract: Glioblastoma therapeutic challenges are in considerable part due to myriad survival adaptations and mechanisms, which allow malignant cells to repurpose signalling pathways within discreet microenvironments. These Darwinian adaptations facilitate invasion into brain parenchyma and perivascular space or promote evasion from repressive factors that represent anti-cancer defence mechanisms. We hypothesised that pre-clinical modelling of glioma invasion by recapitulating early events occurring immediately after surgery at the glioblastoma invasive margin, could reveal the cross-talk between malignant cells and the surrounding healthy astrocytes, which facilitates tumour recurrence. We first generated transgenic H1-derived neural stem cells using CRISPR/Cas9-mediated knock-in of the YFP reporter gene under the control of the GFAP promoter. Reproducible ultrahigh-throughput AggreWells™ (19, 200 micro-wells per 24-well plate) were used to create astrocyte-glioblastoma organoids, which we term 'Gliomasphere Matrices'. YFP-labelled astrocytes were co-cultured with 10 treatment-naïve patient-derived cell lines isolated from the 5-aminolevulinic (5ALA)-determined glioblastoma invasive margin. Co-cultures were seeded upon on a sequentially constructed, time-of-flight secondary ion mass spectrometry (ToF-SIMS)-characterised 3D scaffold, composed of decellularised human brain extract with defined PEGDA hydrogel. YFP-astrocytes were purified from each of the 10 Gliomasphere Matrices using fluorescence-activated cell sorting (FACS) after 6- and 10-days co-culture. RNAseq profiling to address both putative astrocytic reprogramming by invasive glioblastoma cells and gene expression changes intrinsic to tumour cells will be discussed in relation to RNAseq data from patient-derived 5ALA FACS-purified glioblastoma invasive margin tissue. This novel multi-faceted model offers a unique opportunity to recapitulate early molecular cross-talk which facilitates glioblastoma recurrence and may be utilised for high-throughput drug screening.